Multi-objective operation optimization method of microgrid considering the influence of electric vehicle - Tiefeng Xu; Xiaofang Meng; Fangfang Zheng; Yiduo Zhang; Xin Wu; Mingyang Li (Scientific Reports)
Abstract In view of the negative impact on the stable operation of the system caused by the disorderly charging of large-scale electric vehicles connected to the microgrid, an optimization method for the operation of microgrid considering the impact of electric vehicles is proposed. Based on the traditional microgrid, a grid-connected microgrid system with electric vehicles is designed, and the system is studied. Based on Monte Carlo simulation method, the load model of disorderly charging and orderly charging and discharging of electric vehicles is constructed. According to the influence of disorderly charging of electric vehicles, an orderly charging and discharging strategy at time-of-use price is proposed. Taking the minimum total operating cost and the minimum peak-valley difference of the microgrid in one day as the optimization objective, and considering many constraints such as power balance constraints and output constraints of distributed generation units, the multi-objective optimization function is transformed into a single-objective optimization function by linear weighting method, and the model is solved by particle swarm optimization algorithm. Finally, taking the typical daily load data of a micro-grid in a certain area as an example, the comparative results of economic cost and load curve after three scenarios optimization, namely, no EV access, EV access disorderly charging and discharging, are obtained respectively. The calculation results show that the orderly charging and discharging of electric vehicles access to the grid can effectively improve the utilization rate of clean energy, reduce the operating cost and the peak-valley difference of load, and have good practical value.